Uji Aktivitas Antioksidan Ekstrak Etanol Daun Mangga Arum Manis Dengan Metode Dpph - Rusmiyati Dewi; Nur Irmasari (STIKES Columbia Asia Medan, 2023)
Antioxidant compounds will donate one electron to unstable free radicals so that these free radicals can be neutralized and no longer disrupt the body's metabolism (Rahmi, 2017). The human body actually produces several types of antioxidant enzymes, namely superoxide dismutase (SOD), catalase, and glutathione peroxidase, but the amounts are not sufficient to overcome excessive free radicals, so exogenous antioxidants are needed.